The Grand Mosque of Sultan Mahmud Badaruddin II: Acculturation of Islamic Culture in Palembang - Dewi Setyawati & Maya Yunita (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The GrandMosque of Sultan Mahmud II Badarrudin is the largest mosque in Palembang,the architecture is influenced by diverse cultures on every building. This suggests thatacculturation that exists between Palembang and other nations. The building retained itsauthenticity, to be interpreted by future generations as one of the relics of the past thatdescribes multiculturalism in Palembang. Multicultural research in the architecture of theGreat Mosque of Sultan Mahmud II is a qualitative Badarrudin that uses library researchand field research. The research objective is implemented to learners throughmulticultural education through historical relics. The formulation of the problem is howthe culture of other nations affect the architecture of the GrandMosque of Sultan MahmudII Badarrudin Palembang? This study uses culture and multiculturalism with Historicalapproach. Theory used for more in-depth analysis using the theory of semiotics, the theoryof diffusion and acculturation theory. The results of this study the Grand Mosque ofPalembang as a result of the work of Sultan Mahmud Badaruddin monumental in thepresentation of architecture can not be separated from the influence of outside culturesthat entered the archipelago, namely Chinese, Arabic and European (Dutch). As elementsof European culture were clearly visible on the mosque portico.Keywords: The Grand Mosque of Palembang, Multiculturalism, Architecture